The performance of structural foamed concrete with textile reinforcement (TRFC) - Ragrag, Abdalla (2024)
Foamed concrete (FC) has gained substantial interest in the construction sector owing to its lightweight nature, workability, thermal and sound insulation properties, and ease of fabrication. However, FC's high permeability exacerbates corrosion in conventional steel reinforcements. Textile Reinforced Concrete (TRC) presents an innovative alternative, replacing conventional steel with textile reinforcement. Utilizing TRC as reinforcement in foamed concrete offers potential reductions in size, weight, and cost.